El fútbol como fiesta, el balón como bandera - Gloria de los Ángeles Zarza Rondón (Les Cahiers ALHIM)
The scope of football today is undeniable, both in Europe and in Latin America, in fact has become one of the most profitable in the world shows. But not only the relevance of this sport reaches the economic area, but which has gradually been enshrined in a new version of the popular Latin expression “Bread and Circus”. The purpose of this article is to ask how at certain times of the recent history of Latin America Football was an effective element in distract and silence. The feast, the celebration and the excitement generated by this sport in countries such as Argentina, Chile and Uruguay proved to be the best maneuver of the military dictatorships to conceal a sad and tragic reality that still today are struggling to recover.